EXPLORING THE ROLE OF TECHNOLOGY AND TRADITION IN DEVELOPING ENGLISH ORAL PROFICIENCY (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
This study examines the influence of both modern technology and traditional teaching methods on the development of English oral proficiency. With a focus on language acquisition, the research investigates how these two educational approaches complement each other, and how their combined use can enhance the speaking skills of learners.